Dose-dependent effects of vitamin 1,25(OH)2D3 on oxidative stress and apoptosis - Çakıcı, Çağrı; Yiğitbaşı, Türkan; Ayla, Şule; Karimkhani, Hadi; Bayramoğlu, Feyza; Yiğit, Pakize; Kılıç, Ertuğrul; Emekli, Nesrin (Walter de Gruyter GmbH, 2018)
The purpose of this study is to examine the dose-dependent effects of vitamin 1,25(OH)2D3 on apoptosis and oxidative stress. In this study, 50 male Balb/c mice were used as control and experiment groups. The mice were divided into 5 groups each consisting of 10 mice. Calcitriol was intraperitoneally administered as low dose, medium dose, medium-high dose and high dose Vitamin D groups (at 0.5, 1, 5 and 10 µg/kg, respectively), for three times a week during 14 days. At the end of the study, annexin V was measured by enzyme-linked immunosorbent assay method, and total antioxidant capacity and total oxidant status values were measured by colorimetric method in serum. Hematoxylin eosin staining was performed in liver tissues and periodic acid schiff staining was performed in kidney tissues. While comparing the results of medium-high dose (5 µg/kg) and high dose (10 µg/kg) Vitamin D administration to that of the control group, it was observed that serum antioxidant status and annexin V levels decreased and glomerular mesenchial matrix ratio increased in kidney (p<0.05). In addition to these findings, in the group receiving high dose Vitamin D (10 µg/kg), it was observed that the damage to the liver increased together with the the oxidative stress index values (p<0.05). As a result, this study was the first in the literature to report that use of high-dose Vitamin D (10 µg/kg) results in oxidant effect, rather than being an antioxidant, and causes severe histopathological toxicity in the liver and kidney.
Keywords: Apoptosis; Calcitriol; Oxidative Stress; Total Antioxidant Capacity; Total Oxidant Status